Inhibition of LncRNA Kcnq1ot1 suppresses hypoxia-induced pyroptosis of H9C2 cells by regulating miR-27b-3p - Yang, Yingjie; Ou, Yanchun; Mo, Guanlian; Wen, Jing; Liang, Limin; Wang, Shirong; Li, Jinyi (PLOS ONE, 2025)
Background Heart failure (HF) is a major cardiovascular disease with high mortality worldwide, whose pathophysiology is multifaceted. Hypoxia has emerged as a critical factor contributing to the progression of heart failure. We aimed to examine the expression and functions of LncRNA Kcnq1ot1 in hypoxia-induced cardiomyocytes in the process of HF. Methods H9C2 cell model was simulated by hypoxia treatment. TUNEL, ELISA, Western Blot and qRT-PCR assay were carried out to evaluate cell pyroptosis, inflammation and dysfunction. Subsequently, we identified the direct downstream target of Kcnq1ot1 by bioinformatics analysis, RNA pull-down, double Luciferase reporter gene and other functional experiments. Results Firstly, Kcnq1ot1 levels was revealed to be upregulated in hypoxia cells than in control cells, and miR-27b-3p showed the opposite trend. And as expected, inhibition of Kcnq1ot1 and overexpression of miR-27b-3p both protected H9C2 against hypoxia-induced pyroptosis, inflammation and dysfunction. Moreover, miR-27b-3p was proved to bind with Kcnq1ot1 and participated in Kcnq1ot1-mediated H9C2 injury under hypoxia by regulating the Wnt3a/β-Catenin/NLRP3 signaling pathway. Conclusions Collectively, our study demonstrated that inhibition of Kcnq1ot1 protected cardiomyocyte against hypoxia-induced injury possibly via sponging miR-27b-3p, which could be useful as biomarkers and therapeutic targets for HF patients.